Randomized clinical trials towards a single‐visit cure for chronic hepatitis C: Oral GSK2878175 and injectable RG‐101 in chronic hepatitis C patients and long‐acting injectable GSK2878175 in healthy participants. Issue 7 (18th March 2020) - Deng, Yanli; Campbell, Fiona; Han, Kelong; Theodore, Dickens; Deeg, Mark; Huang, Michael; Hamatake, Robert; Lahiri, Soumi; Chen, Shuguang; Horvath, Gabor; Manolakopoulos, Spilios; Dalekos, George N.; et al.
Abstract: Single‐visit cures for chronic hepatitis C are lacking. We conducted two clinical studies towards the goal of developing a regimen for single‐visit cure. In a randomized, open‐label, Phase 2 study (RG101‐04), investigators enrolled 26 adult chronic hepatitis C patients to evaluate safety and efficacy of single subcutaneous injection of RG‐101 (4 mg/kg) and daily oral tablets of GSK2878175 (20 mg) for 6, 9 or 12 weeks. In another randomized, double‐blind, single dose Phase 1 study (RG101‐06), investigators enrolled 18 healthy men to assess safety and PK of GSK2878175 long‐acting injectable at 100, 200 or 400 mg. In RG101‐04, SVR48 rates were 50%, 56% and 89%, for the 6, 9 and 12 weeks treatment arms, respectively. All AEs were mild or moderate in severity (≤Grade 2). In RG101‐06 at 400 mg, the mean duration of GSK2878175 plasma levels above in vitro therapeutic concentrations for GT1b was 41 days. All AEs were Grade 2 or less. In conclusion, single injection of RG‐101 combined with 12 weeks of GSK2878175 oral tablets was generally well tolerated and resulted in high SVR rates in chronic hepatitis C patients. Single injections of GSK2878175 long‐acting injectable were also well tolerated; however, higher doses would be required if used in combination with RG‐101 to achieve the SVR rates observed in the oral combination study to enable a single‐visit curative regimen.